The Design and Implementation of High Precision Three-Phase Sine-Wave Signal Generator - Wu, Di; Li, Shan Shan; Zheng, Shi; Kang, Shou Qiang (Applied Mechanics and Materials, 2014)
A design and implementation method of high precision three-phase sine-wave signal generator is proposed based on MCU and FPGA. For the traditional design method, direct analog synthesis method and phase locked loop (PLL) technology are used to design the signal generator. So the function, the precision and other aspects are inadequate. Aiming to the problem, a signal generator is designed based on direct digital frequency synthesis (DDS) technology. The MCU is used to control the peripheral devices and the frequency and phase control word can be obtained. The DDS module is achieved by EP4CE6E22C8 and the waveform lookup table addresses are outputted. The digital three-phase sine-wave data can be read from the lookup table. Through the three-way D/A converter and the amplifier circuit, the digital signal is converted to analog signal and the three-phase sinusoidal wave is outputted. The precision can be improved by increasing the sampling points, phase accumulator bits and D/A bits, and then, high precision three-phase sine-signal can be obtained and the adjustable frequency precision is 0.001.